MENGALIR DAN MEMBAUR SEBUAH KARYA AKULTURASI MUSIK MINANGKABAU-JAWA - Iwan Budi Santoso; Teti Darlenis; Dana Adi Arya Pradipta (Surakarta: Jurusan Karawitan Institut Seni Indonesia Surakarta, 2023)
Artistic Research (Art Creation) entitled Flowing and Blending was inspired by the movement and/or migration of Indonesian people from one area to another. This is based on the necessities of life in the area of origin which are considered no longer providing income, so that it has an impact on economic income. The arrival of migrants from an area makes the problem of the culture of origin and those visited sometimes unable to merge. The purpose of this artistic research is to find out the different tone areas. However, in the work Menglir dan Mebaur produces a mixture of musical sounds as measured by the sound ambitus of the instrument when used in cultural communication (music). The process of mutual respect and respect by using the language of communication will be able to flow and blend in the cultural frame, even though both have different backgrounds. Based on the elements of culturalcommunication, it produces cross-cultural values that are mutually respectful and respectful. Musical artwork Flows and Diffuses becomes a manifestation of musical works representing two different cultural elements, however, they can complement each other with the communication language of musical instrument tones when sung. In order to build the musical in this part of the work as a whole, the authors also look for elements of the combination of two cultures, namely Minang and Javanese, with the hope that the concept of assimilation can become a unified musical feeling as amirror or reflection of a togetherness.